Solvent dependent photophysics of fac-[Re(CO)3(11,12-X2dppz)(py)]+ (X = H, F or Me) - KELLY, JOHN MOFFAT (My University, 2007)
The photophysical properties of [Re(CO)3(dppz)(py)]+ (dppz = dipyrido-[3,2-a:2 ,3 -c] phenazine) (1) and its 11,12 substituted derivatives [Re(CO)3(dppzMe2)(py)]+ (2) and [Re(CO)3(dppzF2)(py)]+ (3) have been examined in organic and aqueous environments using phosphorescence and picosecond transient visible and infrared absorption spectroscopic methods. The roles of the intraligand IL(p?p*) and metal-to-ligand charge transfer MLCT(phz) excited states are evaluated and used to explain the major effect of difluoro-substitution, which is particularly remarkable in water, where the excited state of [Re(CO)3(dppzF2)(py)]+ (3) is strongly quenched.
PUBLISHED
Keywords: difluoro-substitutio; difluoro-substitutio